Biblioteki oświatowe i publiczne w Łodzi w dwudziestoleciu międzywojennym - Kaczmarek, Iwona (Acta Universitatis Lodziensis. Folia Librorum, 2013)
Lodz of the interwar period was the second, after the capital, most populous city of the Second Republic of Poland. After regaining independence, the population of the city was about 300,000 inhabitants. In 1919 there were about 80 large libraries of various types in the area of Lodz. They included: the Public Library, public libraries run by cultural and educational societies, libraries run by social and cultural associations, libraries run by trade unions and professional associations as well as libraries at schools. These places faced a lot of financial perplexities as well as housing problems. An important achievement of the Lodz librarianship of the twenty year interwar period was to carry out the concept of the inter-municipal library network with the Public Library as the central research library, places to borrow books for children, adolescents and adults. The author of the project presented in 1921 at the meeting of the Cultural and Educational Magistrate was Jan Augustyniak.